2022
DOI: 10.3389/fonc.2022.858189
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Outcomes of Video-Assisted Thoracoscopic Surgery Versus Open Thoracotomy After Neoadjuvant Chemoimmunotherapy in Resectable NSCLC

Abstract: BackgroundNeoadjuvant chemoimmunotherapy becomes more widespread in the treatment of NSCLC, but few studies have reported the details of surgical techniques and perioperative challenges following neoadjuvant chemoimmunotherapy until now. The primary aim of our study was to address the feasibility and safety of pulmonary resection after neoadjuvant chemoimmunotherapy via different surgical approaches, video-assisted thoracoscopic surgery (VATS) and open thoracotomy.MethodsPatients with an initial diagnosis of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 24 publications
4
24
1
Order By: Relevance
“…Recent publications have shown that MIS is associated with a faster postoperative recovery over thoracotomy for NSCLC patients following induction therapy than thoracotomy [30,31]. Of note, our study revealed that MIS also shortened chest tube duration than open lobectomy, suggesting that this advantage of MIS also exists for patients with immunochemotherapy induction, which was in line with a previous study but con icted with another [20,28]. Moreover, we found that the two surgical approaches led to similar postoperative hospitalization.…”
Section: Discussionsupporting
confidence: 91%
“…Recent publications have shown that MIS is associated with a faster postoperative recovery over thoracotomy for NSCLC patients following induction therapy than thoracotomy [30,31]. Of note, our study revealed that MIS also shortened chest tube duration than open lobectomy, suggesting that this advantage of MIS also exists for patients with immunochemotherapy induction, which was in line with a previous study but con icted with another [20,28]. Moreover, we found that the two surgical approaches led to similar postoperative hospitalization.…”
Section: Discussionsupporting
confidence: 91%
“…16 While several articles have mentioned the use of MIS in the surgical treatment of lung cancer patients after immunotherapy, 16,17 reports directly comparing MIS with thoracotomy have been limited. Recently, Zhang et al 18 conducted a retrospective study among stage IB-IIIB lung cancer patients and found that VATS achieved comparable efficacy to open surgery, with shorter ICU stays for patients, indicating the safety, efficacy, and feasibility of VATS as a surgical strategy for patients after immunotherapy. 19 Our results similarly demonstrated that patients who underwent MIS after immunotherapy had equally favorable prognoses to those who underwent thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
“…The result indicates that radiotherapy or chemoradiotherapy could increase the risk of pulmonary complications ( 24 ). However, neither chemoimmunotherapy nor chemotherapy has been reported to pose a negative effect on postoperative recovery of sleeve resections ( 25 , 26 ). In the presented case, the patient received neoadjuvant immunotherapy alone and manifested a smooth postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%